2013
DOI: 10.1083/jcb.201306012
|View full text |Cite
|
Sign up to set email alerts
|

Atrophin–Rpd3 complex represses Hedgehog signaling by acting as a corepressor of CiR

Abstract: Atrophin suppresses Hedgehog signaling by interacting with the transcriptional effector CiR and recruiting the histone deacetylase Rpd3 to the dpp locus to repress its transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 43 publications
4
39
1
Order By: Relevance
“…In this screening, UbcD1 , also known as effete/eff , was identified as a negative regulator of Ci. Compared with control, Ci FL proteins accumulate, especially in the dorsal part of UbcD1 RNAi wing disks (Fig B and C), which is consistent with previous studies indicating that MS1096‐Gal4 has a higher transcriptional activity in the dorsal compartment compared with the ventral compartment . In response to Ci FL accumulation, the expression of dpp , one of the Hh target genes, was elevated as indicated by both real‐time qPCR analyses (Fig D) and dpp ‐LacZ staining (Fig E–F′), suggesting the up‐regulation of Hh signaling activity.…”
Section: Resultssupporting
confidence: 90%
“…In this screening, UbcD1 , also known as effete/eff , was identified as a negative regulator of Ci. Compared with control, Ci FL proteins accumulate, especially in the dorsal part of UbcD1 RNAi wing disks (Fig B and C), which is consistent with previous studies indicating that MS1096‐Gal4 has a higher transcriptional activity in the dorsal compartment compared with the ventral compartment . In response to Ci FL accumulation, the expression of dpp , one of the Hh target genes, was elevated as indicated by both real‐time qPCR analyses (Fig D) and dpp ‐LacZ staining (Fig E–F′), suggesting the up‐regulation of Hh signaling activity.…”
Section: Resultssupporting
confidence: 90%
“…Through Co-IP experiments, we confirmed that zebrafish Usp7 (zUsp7) could bind zebrafish Gli proteins (zGli1, zGli2 and zGli3) (Figures S6A-C). Next, we examined the expression levels of several Hh-responsive genes, including patched2 ( ptch2 ), forkhead4 ( fkd4 ), NK2 homeobox 2b ( nkx2.2b ), and hedgehog interacting protein ( hhip ), in control or zusp7 morpholino treated zebrafish embryos 24h postfertilization (hpf) by in situ hybridization and real-time PCR (Zhang et al, 2013a). Compared with control morphants (Figures 7F, G, H, I), Hh target gene expression was notably down-regulated in zusp7 morphants (Figures 7F’, G’, H’, I’).…”
Section: Resultsmentioning
confidence: 99%
“…The in situ hybridization of zebrafish embryos were carried out based on the previously described protocol (Thisse and Thisse, 2008; Zhang et al, 2013a). In brief, zebrafish embryos were obtained by natural spawning of adult AB strain zebrafish.…”
Section: Methodsmentioning
confidence: 99%
“…The combined activity of these kinases on GLI2/3 and Ci ultimately leads to binding of E3 SCF ubiquitin ligase and processing of GLI2 and GLI3 to their truncated repressor forms [8, 22, 2632]. The mechanisms by which GLI proteins repress target genes is poorly understood, but includes histone deacetylation [33]. …”
Section: Processing Of Gli Proteins Into Transcriptional Repressorsmentioning
confidence: 99%